Method of identification of physiology descriptions for the system of the distance determination of emotional state of the special divisions fighters of the Ministry of Internal Affairs - Belzetskyi, R. S.; Shyian, A. A. (Visnyk of Vinnytsia Politechnical Institute, 2013)
A method for identification of physiology descriptions of the psycho physiological state of the human is offered in the paper. The subject domain of activity of individual, characteristic for activity of fighters of the special division of the Ministry of Internal Affairs is thoroughly investigated. The series of experiments on the imitator of battle situations proved, that frequency of heart rate of man was an informing factor that allows identifying a type of battle situations. In the conditions of experiment the frequency of heart rate was determined exactly by the emotional status of the fighter. The frequency of breathing is considered to be the less informative factor which also should be taken into consideration.